Aberrant Dynamics of Regional Coherence Measured by Resting-State fMRI in Children With Benign Epilepsy With Centrotemporal Spikes (BECTS) - Jiang, Lin; Ma, Xuejin; Liu, Heng; Wang, Ji; Zhang, Jiaren; Zhang, Guoming; Li, Shiguang; Zhang, Tijiang (Frontiers in Neurology, 2021)
Objective: To explore the dynamic features of intrinsic brain activity in children and adolescents with benign epilepsy with centrotemporal spikes (BECTS) and examine whether these indexes were associated with behaviors. Methods: Twenty-six children with BECTS (10.35 ± 2.91 years) and 26 sex-, and age-matched (11.35 ± 2.51 years) healthy controls (HC) were recruited and acquired resting-state functional magnetic resonance imaging (rs-fMRI) and behavioral data. Dynamic regional homogeneity (dReHo), including mean and coefficient of variation (CV) metrics derived from the rs-fMRI data, were compared between the BECTS and the HC groups. Results: Significantly decreased mean dReHo in bilateral supramarginal gyrus, left middle temporal gyrus (MTG.L), left postcentral gyrus and superior occipital gyrus were found in children with BECTS. Meanwhile, increased CV of dReHo in MTG.L and right fusiform in children with BECTS was revealed compared with HC. Further association analyses showed CV of dReHo in MTG.L was positively associated with age and negative correlation was found between mean dReHo of MTG.L and disease duration. Besides, CV of dReHo in MTG.L was found positively associated with the intelligence quotient (IQ) language scores and full IQ scores in children with BECTS, as well as CV of dReHo in left inferior temporal gyrus and rolandic operculum were positively correlated with IQ operation scores and full IQ scores. Conclusion: Aberrant dynamic regional coherence sin sensorimotor, linguistic, and lateral temporal regions suggests dynamical interplay that underlying cognitive performance in children with BECTS, suggesting an intrinsic dynamic mechanism for BECTS.